Improving legume yield through inoculant technology and partnership - International Livestock Research Institute (International Livestock Research Institute, 2019)
Grain legumes are particularly attractive to low input systems of agriculture because they take inert nitrogen from the air and (through root nodule bacteria known as rhizobia) transform it into proteins in a process that leaves no carbon footprint. The N2Africa project is delivering inoculant technology to small-scale farmers for enhancing grain legume production and soil fertility in Ethiopia.